They called us exceptional : and other lies that raised us - Gupta, Prachi (Journalist) (Crown, 2023)
"An Indian American daughter reveals how the dangerous model minority myth fractured her family in this searing, brave memoir. How do we understand ourselves when the story about who we are supposed to be is stronger than our sense of self? What do we stand to gain--and lose--by taking control of our narrative? These questions propel Prachi Gupta's heartfelt memoir, and can feel particularly fraught for many immigrants and their children who live under immense pressure to belong in America. Family defined the cultural identity of Prachi and her brother, Yush, connecting them to a larger Indian American community amid white suburbia. But their belonging was predicated on a powerful myth: that Asian Americans, and Indian Americans in particular, have perfected the alchemy of middle-class life, raising tight-knit, high-achieving families that are immune to hardship. Molding oneself to fit this image often comes at a steep, but hidden, cost. In They Called Us Exceptional, Gupta articulates the dissonance, shame, and isolation of being upheld as an American success story while privately navigating traumas invisible to the outside world. Gupta addresses her mother throughout the book, weaving a deeply vulnerable personal narrative with history, postcolonial theory, and research on mental health to show how she slowly made sense of her reality and freed herself from the pervasive, reductive myth that had once defined her. But tragically, the act that liberated Gupta was also the act that distanced her from those she loved most. By charting her family's slow unraveling and her determination to break the cycle, Gupta shows how traditional notions of success keep us disconnected from ourselves and one another-and passionately argues why we must orient ourselves toward compassion over belonging"--